Requiem for a dream [videorecording (DVD)] - Aronofsky, Darren; Burstyn, Ellen, 1932-; Leto, Jared, 1971-; Connelly, Jennifer; Shelby, Hubert (Artisan Home Entertainment, 2001)
Harry, his best friend Tyrone, his girlfriend Marion, and his mother all struggle with drug addiction against a backdrop of the abandoned beaches and faded glory of Coney Island, Brooklyn.